PENGGUNAAN KACANG TANAH DALAM PEMBUATAN TAHU SUSU LEMBANG - Surya Aditya; Ghini Kuntala devi (Journal of Innovation Research and Knowledge, 2024)
This study aims to find out the use of peanuts in the production of Lembang milk tofu, determine the nutritional content produced in the use of peanuts in the production of Lembang milk tofu and find out the comparison of the details of the production cost of the use of peanuts in the production of Lembang milk tofu with the comparator. The data collection techniques carried out are by means of product experiments, questionnaire distribution, and observation. Meanwhile, the data analysis technique uses a Likert scale. The author concludes about the use of peanuts in the manufacture of Lembang milk tofu: milk tofu that uses peanuts in terms of appearance, aroma and texture should be further improved. The advice given for problem solving is necessary Adaya:1. The processing of making milk tofu must use professional tools so that the taste and texture produced are better 2. The use of peanuts to be used as an alternative food substitute for soybeans, so that it can reduce imports